1974
DOI: 10.1159/000208219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Platelet Count, Adhesion, and Aggregation

Abstract: 15 min of strenuous exercise caused a highly significant rise in the venous platelet count without altering platelet adhesion to glass. It also produced a significant increase in the rate of the second phase of ADPand adrenaline-induced aggregation, 5-HT-induced aggregation and disaggregation, and collagen-induced aggregation. These changes in platelet number and function following exercise should be taken into account when anti-platelet drugs are assessed in human subjects, and when changes in these parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 14 publications
1
11
1
1
Order By: Relevance
“…Our results did not confirm the findings of an increased platelet aggregation immediately after short-term strenuous exercise observed by other authors in healthy persons and coronary artery disease patients (Hyers et al, 1980;Warlow and Ogston, 1974). Three Downloaded by [La Trobe University] at 13:12 13 June 2016 minutes after exercise there were no significant changes in the initial and total induced platelet aggregation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results did not confirm the findings of an increased platelet aggregation immediately after short-term strenuous exercise observed by other authors in healthy persons and coronary artery disease patients (Hyers et al, 1980;Warlow and Ogston, 1974). Three Downloaded by [La Trobe University] at 13:12 13 June 2016 minutes after exercise there were no significant changes in the initial and total induced platelet aggregation.…”
Section: Discussioncontrasting
confidence: 99%
“…Although physical activity is widely recognised as being beneficial to health, attempts to relate the effects of exercise to changes in platelet aggregation and functions have produced conflicting results. For example, some studies have reported that strenuous exercise results in increased platelet aggregation in response to adenosine diphosphate (ADP),f77-85] collagen [71,78,80,841 and adrenaline,f 74 1 Similarly, maximal cycling exerciseI76, 83,85] and maximal treadmill running! ?I] resulted in a significant activation of platelets as manifested by an increased sensitivity to ADPinduced aggregation, Radioimmunoassays of the plasma levels of ~-TG and platelet factor 4; plateletspecific proteins liberated from a-granules during activation, have been used as markers to assess the degree of platelet activation,186,87] Todd et al,l88] demonstrated a significant increase in platelet aggregability as reflected by an increase in plasma level of ~-TG in elderly men after treadmill exercise at 70 to 75% V02max, Other studies showed that strenuous exercise causes an increase in plasma level of ~_TGI16,18,66,76,81 ,84,[89][90][91][92][93] and platelet factor 4, [76,89,[93][94][95] Additional markers pertinent to platelet activation such as a-granule membrane protein [91] and thromboxane (TX) B2 were also increased after exercise,l88, 91,92] It has been suggested that exercise-induced activation of platelets might be linked with anaerobic metabolism for energy production during exercise.…”
Section: Platelet Count and Functionsmentioning
confidence: 99%
“…Alguns estudos em humanos demonstraram aumento de 18 a 80% do número de plaquetas após sessões de exercício na esteira e em bicicleta, de acordo com o esforço (Warlow, Ogston, 1974;Metha, Metha, 1982;Davis et al, 1990;Wang et al, 1994). O exercício físico exerce efeito sobre vários fatores da coagulação e fibrinolíticos, bem como sobre a função das plaquetas no sangue.…”
Section: Resultsunclassified